A review on socio-economic aspects of sustainable biofuels. (2016) - Azad, Abul Kalam; Rasul, Mohammad G.; Khan, M. Masud K.; Sharma, Subhash C.; Bhuiya, M. Mostafa K.; Mofijur, M.
Biofuels are renewable eco-fuel, produced from biological resources. They are classified into 1st, 2nd and 3rd generations based on their feedstocks. The 2nd and 3rd generation biofuels are called advanced and sustainable biofuel. The study reviewed and discussed about socio-economic aspects of the sustainable biofuel in Australia because economy is seen to be a key driver for use of biofuels. Recent researches focused on sustainable biofuel production, their commercialisation worldwide. The world biofuel scenario is presented in this study which shows that total biofuel production is progressively moving towards advanced biofuels. Australian total biofuel production, consumption and available present production facilities are also outlined. The study briefly discussed about Australian energy economy such as energy export, import and trades etc. The study concluded that the 2nd generation biofuel can be considered as sustainable alternatives to petroleum fuel in transport sector providing great economic and environmental benefits to Australia.